2021
DOI: 10.1038/s41598-021-03602-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of valve endocarditis in high-risk patients and predictors of long-term outcomes

Abstract: Infective endocarditis represents a surgical challenge associated with perioperative mortality. The aim of this study is to evaluate the predictors of operative mortality and long-term outcomes in high-risk patients. We retrospectively analyzed 123 patients operated on for infective endocarditis from January 2011 to December 2020. Logistic regression model was used to identify prognostic factors of in-hospital mortality. Long term follow-up was made to asses late prognosis. Preoperative renal failure, an eleva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Reasons for nonsurgical treatment included; poor prognosis (33.7%), death before surgery (23.3%), stroke (22.7%), sepsis (21%) and hemodynamic instability (19.8%) 2 . In another retrospective study of 123 patients operated for IE, a 27% in‐hospital mortality was found in patients who had undergone prior aortic valve replacement ( p = 0.01), operated on active phase of IE versus after acute phase (16% vs. 0%, p = 0.02), and increased cross clamp time significantly affected survival rate (mean cross‐clamp time 135 ± 65 min in dead vs. 76 ± 32 min in surviving patients; p = 0.0005) when followed for mean of 57.94 ± 30.9 months 3 . While these high‐risk cohort of patients in the acute phase of IE are not offered valve surgery due to high surgical mortality risk, without surgery, they have a significantly high in‐hospital morbidity and mortality and are often placed on palliative care measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for nonsurgical treatment included; poor prognosis (33.7%), death before surgery (23.3%), stroke (22.7%), sepsis (21%) and hemodynamic instability (19.8%) 2 . In another retrospective study of 123 patients operated for IE, a 27% in‐hospital mortality was found in patients who had undergone prior aortic valve replacement ( p = 0.01), operated on active phase of IE versus after acute phase (16% vs. 0%, p = 0.02), and increased cross clamp time significantly affected survival rate (mean cross‐clamp time 135 ± 65 min in dead vs. 76 ± 32 min in surviving patients; p = 0.0005) when followed for mean of 57.94 ± 30.9 months 3 . While these high‐risk cohort of patients in the acute phase of IE are not offered valve surgery due to high surgical mortality risk, without surgery, they have a significantly high in‐hospital morbidity and mortality and are often placed on palliative care measures.…”
Section: Introductionmentioning
confidence: 99%
“…when followed for mean of 57.94 ± 30.9 months. 3 While these highrisk cohort of patients in the acute phase of IE are not offered valve surgery due to high surgical mortality risk, without surgery, they have a significantly high in-hospital morbidity and mortality and are often placed on palliative care measures. Thus, a percutaneous approach for mitral valve (MV) IE debulking may be an alternative therapeutic option if able to be performed in a predictable manner.…”
mentioning
confidence: 99%
“…Habib et al In the EURO-ENDO registry, from 1 January 2016 to 31 March 2018, centers were asked to include consecutive patients aged greater than 18 years who presented with IE during a 1-year period [21]. A total of 156 centers from 40 countries included 3116 cases of IE, representing an average of 20.19 patients per center per year offers a unique opportunity to assess the current characteristics of IE in Europe [22]. It allows us to consider clinical presentation, microbiology, complications, management, and prognosis.…”
Section: Epidemiologymentioning
confidence: 99%
“…Surgery can be required however also cannot be a treatment option due to patient refusal, high surgical risk, neurological complications, or death before surgery (Ortiz-Bautista et al, 2017;Habib et al, 2019). In-hospital mortality following surgery was highest for PVE (up to 27%) when compared to NVE (16%) and CDRIE (8-15%) (Ortiz-Bautista et al, 2017;Habib et al, 2019;Nasso et al, 2021).…”
Section: Surgerymentioning
confidence: 99%
“…Additionally, fungal endocarditis can occur up to 3 years following surgery ( Shokohi et al, 2014 ). The post-surgical 30-day mortality for PVE is 14–20% and at 1-year 22–36% ( Pyo et al, 2021 ; Weber et al, 2021 ), with 27% in-hospital mortality in patients with a prior aortic valve replacement ( Nasso et al, 2021 ). For both NVE and PVE, the type of prosthesis (biological or mechanical) chosen is not associated with mortality while (longer) aortic cross-clamp times are a significant mortality predictor ( Nasso et al, 2021 ).…”
Section: Treatment and Outcomesmentioning
confidence: 99%